Pengaruh Metode Tugas Kelompok Terhadap Hasil Belajar Siswa Kelas V Sekolah Dasar Pada Pembelajaran IPA Tema Panas Dan Perpindahannya - Luqman, Khamidatus Sholikhah; Kamidjan, Kamidjan; Wiyadi, Heru (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
In the science learning, we often use conventional method and learning evaluation which only assesses the results of individual assignments. So, the science learning is less varied and also less in increasing the students’ achievement. The purpose of this study is to identify the student learning outcomes before and after using group assignment method and to determine the effect of learning outcomes using group assignment method. The research approach used is quantitative experimental research with one group pretest-posttest design. The data collection techniques is in the form of test, observation and documentation. The data analysis used is validity test, reliability test, normality test and hypothesis test. The results showed that the learning outcomes of the average score of students in the pretest was 69.33 and the posttest was 87.26. The results of the analysis showed that the pretest and posttest with paired sample t test by using SPSS version 16 known Sig values. (2-tailed) is 0,000 <0.05. It can be concluded that Ho is rejected and Ha is accepted which means there is influence of the group assignment method on the learning outcomes of Grade V students in science learning.